Factors affecting reproductive performance of Zebu and crossbred cows under small-scale dairy farms - Kassa, T.; Tegegne, Azage (1998)
Data on reproductive performance of Zebu and Friesian X Zebu crossbred cows reared under small-scale dairy farms were analysed and the effects of genotype, parity, body condition score (BCS), season, and year of calving were examined for a total of 246 calvings. Uterine involution was completed earlier in Zebu (23.8 (+ or -) 1.2 days) than in crossbred (31.4 (+ or -) 1.3 days) and in primiparous (25.4 (+ or -) 2.0) than in pluriparous (29.7 (+ or -) 0.8 days) cows (P<0.05). Body condition score, season, and year of claving had no effect on uterine involution (P>0.05) by BCS at calving but not by parity, season, and year of calving. The interval between calving and days) than in Zebu (183.2 (+ or -) 11.7 days). The overall mean for calving interval was 509.7 days and there was an effect of year of calving (P<0.05). It was concluded that BCS and genotype affected the duration from calving to resumption of ovarian activity and conception, respectively.